Tinjauan Historis Pengungsian Vietnam di Pulau Galang 1979-1996 - Hendri, Zendri; Dandi, Rahmad (MAN 4 Kota Pekanbaru, 2022)
Vietnam's long history starts from the effort to gain independence from France, the prolonged civil war between Communist North Vietnam and nationalist South Vietnam, to the Vietnamese invasion of Cambodia, which led to the massive migration of Vietnamese people to various countries using boats so that refugees This Vietnamese, known as the